Impella support as a bridge to heart surgery in patients with cardiogenic shock. (4th April 2022) - Saito, Shunsuke; Shibasaki, Ikuko; Matsuoka, Taiki; Niitsuma, Ken; Hirota, Shotaro; Kanno, Yasuyuki; Kanazawa, Yuta; Tezuka, Masahiro; Takei, Yusuke; Tsuchiya, Go; Konishi, Taisuke; Ogata, Koji; et al.
Abstract: OBJECTIVES: In patients with cardiogenic shock, delayed surgery after stabilization of haemodynamics and improvement in end-organ function by mechanical circulatory support is known to yield better outcomes than emergency surgery. We aimed to investigate the effectiveness of Impella (Abiomed, Danvers, MA, USA) as a bridge to cardiac surgery in patients with cardiogenic shock. METHODS: We reviewed 7 patients with cardiogenic shock who underwent Impella support as a bridge to cardiac surgery using cardiopulmonary bypass at our institution between April 2018 and August 2021. RESULTS: Cardiogenic shock was caused by ventricular septal rupture in 3 patients, papillary muscle rupture in 1 and acute myocardial infarction in 3. Cardiac surgery was delayed by 1–7 (3.9 ± 2.5) days with Impella support after the diagnosis of cardiogenic shock, during which the hepatic and renal function of the patients improved significantly. Device-related or operation-related adverse events included re-exploration for bleeding in 3 patients, acute limb ischaemia due to thromboembolism in 1 and intraoperative aortic dissection in 1. Thirty-day mortality was 14.3%, and the cumulative survival was 71.4% at 1 year. The survival tended to be better than that in historical control group in which extracorporeal membrane oxygenation was used as a bridge to surgery ( P = 0.0992). CONCLUSIONS: Impella is an effective tool for bridging patients with cardiogenic shock to surgery. This strategy may improve surgical outcomes in patients with cardiogenic shock. However, prolonged Impella support may increase significant adverse events, and further investigation is required to determine the optimal duration of support before surgery. Abstract : Emergency heart surgery using cardiopulmonary bypass in patients with cardiogenic shock is associated with high mortality and poor clinical outcomes [1–3].